The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/genes13091611
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer-Adjacent Tissues Express Higher Levels of Cancer-Promoting Genes than the Matched Tumors

Abstract: Molecular alterations in tumor-adjacent tissues have recently been recognized in some types of cancer. This phenomenon has not been studied in endometrial cancer. We aimed to analyze the expression of genes associated with cancer progression and metabolism in primary endometrial cancer samples and the matched tumor-adjacent tissues and in the samples of endometria from cancer-free patients with uterine leiomyomas. Paired samples of tumor-adjacent tissues and primary tumors from 49 patients with endometrial can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…Our data indicate that the regulation of angiogenesis-related genes in EC with prognostically less favourable characteristics is not limited to T tissue alone but rather spreads onto the non-cancerous TA tissue of the surrounding endometrium. This is in accordance with the fact that TA tissues are often involved in the development and progression of the tumour [70][71][72]. TA tissue is a distinct tissue type that presents a unique intermediate state between healthy tissue and tumour tissue [72].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our data indicate that the regulation of angiogenesis-related genes in EC with prognostically less favourable characteristics is not limited to T tissue alone but rather spreads onto the non-cancerous TA tissue of the surrounding endometrium. This is in accordance with the fact that TA tissues are often involved in the development and progression of the tumour [70][71][72]. TA tissue is a distinct tissue type that presents a unique intermediate state between healthy tissue and tumour tissue [72].…”
Section: Discussionsupporting
confidence: 80%
“…The neoplastic and non-neoplastic cells in the microenvironment communicate to produce a microenvironment favourable for the progression of endometrial carcinogenesis [43,45]. According to different lines of evidence, genomic data from non-cancerous TA tissue can independently predict cancer survival, and, in some cases, provide even superior performance relative to models based on tumour-derived data alone [71,73,74]. We found fewer differences between angiogenesisrelated gene expression in T versus TA tissue in higher stages and grades of EC, indicating that the progression of the tumour was not only related to the expression of AFs in the tumorous tissue but also to the expression in the TA tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have highlighted molecular changes in tumor-adjacent “normal” tissues in several types of cancer. For instance, the tissues surrounding endometrial cancer express higher levels of tumor-promoting proteins than the matched tumors do 24 . In hepatocellular carcinoma, peritumoral liver tissues were found to exhibit a specific metabolic phenotype by proteomic analysis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of these enzymes can induce apoptosis, cell cycle arrest, and differentiation. TWIST1 is listed as a transcriptional regulator at CIDR +12 h: this gene is associated with cancer metabolism and regulates the epithelial-to-mesenchymal transition [ 100 ]. The role of these regulators is consistent with the top diseases and functions categories that include Cancer , Cellular growth and proliferation and Organismal injury and abnormalities , supporting the cellular growth essential to the increased endometrial thickening observed in the bovine follicular phase in both natural and induced oestrus [ 74 ].…”
Section: Discussionmentioning
confidence: 99%